Coronary artery disease in patients with body mass index ≥30 kg/m2: a retrospective chart analysis. Issue 3 (1st January 2016) - Alkhawam, Hassan; Nguyen, James; Sayanlar, Jason; Sogomonian, Robert; Desai, Ronak; Jolly, JoshPaul; Vyas, Neil; Syed, Umer; Homsi, Maher; Rubinstein, David
Abstract : Objective: In this study, we evaluated obesity as a single risk factor for coronary artery disease (CAD), along with the synergistic effect of obesity and other risk factors. Methods: A retrospective study of 7, 567 patients admitted to hospital for chest pain from 2005 to 2014 and underwent cardiac catheterization. Patients were divided into two groups: obese and normal with body mass index (BMI) calculated as ≥30 kg/m 2 and <25, respectively. We assessed the modifiable and non-modifiable risk factors in obese patients and the degree of CAD. Results: Of the 7, 567 patients who underwent cardiac catheterization, 414 (5.5%) had a BMI ≥30. Of 414 obese patients, 332 (80%) had evidence of CAD. Obese patients displayed evidence of CAD at the age of 57 versus 63.3 in non-obese patients ( p <0.001). Of the 332 patients with CAD and obesity, 55.4% had obstructive CAD versus 44.6% with non-obstructive CAD. In obese patients with CAD, male gender and history of smoking were major risk factors for development of obstructive CAD ( p =0.001 and 0.01, respectively) while dyslipidemia was a major risk factor for non-obstructive CAD (p=0.01). Additionally, obese patients with more than one risk factor developed obstructive CAD compared to non-obstructive CAD ( p =0.003). Conclusion: Having a BMI ≥30 appears to be a risk factor for early development of CAD. Severity of CAD in obese patients is depicted on non-modifiable and modifiable risk factors such as the male gender and smoking or greater than one risk factor, respectively.